Fatores críticos associados à implantação de programas de aceleração corporativa em organizações - Gilvan Augusto Silva (2018)
With the arrival of Industry 4.0 and with the high level of competitiveness, big companies began to look for innovative alternatives to put themselves ahead of their competitors, based on the reduction of costs, the increase of efficiency and consequently the increase in profitability. One of the most important initiatives that "established companies" have developed today is the open innovation, which aims to bring into the organization external innovative solutions that are aligned with its strategic plan (inbound), as well as offering other companies innovative solutions developed internally (outbound). Looking at the global advancement in number and quality of startups solutions, established companies are opening their doors to open innovation through so-called "Corporate Acceleration Programs." With the recent increase of this type of program, it is necessary to carry out research on the subject, so that good practices can be identified and knowledge consolidated, in order to minimize the risk of undesirable results. The general objective of this dissertation is to evaluate the critical and complementary factors that hinder or impel the implementation of corporate acceleration programs, under the perception of actors in the light of recent local experiences. For this, a multiple case analysis was conducted, based on a concomitant descriptive quantitative / qualitative research with 20 leaders and participants of corporate acceleration initiatives in Brazil, 10 from established companies and 10 from startups. As a result, the study identified 16 critical factors for the implementation of corporate acceleration programs and offered recommendations to established companies, aiming at obtaining better results in this type of program. This work contributes to broadening the discussion about the critical factors that hinder or impel the implementation of corporate acceleration programs and the means to obtain the best possible results in these programs